An Upgraded, Highly Saturated Linkage Map of Japanese Plum (Prunus salicina Lindl.), and Identification of a New Major Locus Controlling the Flavan-3-ol Composition in Fruits - Battistoni, Benjamín; Salazar, Juan; Vega, Wladimir; Valderrama-Soto, Diego; Jiménez-Muñoz, Pablo; Sepúlveda-González, Ailynne; Ahumada, Sebastián; Cho, Isaac; Gardana, Claudio Sebastiano; Morales, Héctor; Peña-Neira, Álvaro; Silva, Herman; et al. (Frontiers in Plant Science, 2022)
Japanese plum fruits are rich in phenolic compounds such as anthocyanins and flavan-3-ols, whose contents vary significantly among cultivars. Catechin (C) and epicatechin (EC) are flavan-3-ols monomers described in fruits of this species and are associated with bitterness, astringency, antioxidant capacity, and susceptibility to enzymatic mesocarp browning. In this research, we aimed to identify quantitative trait loci (QTL) associated with the flavan-3-ol content in Japanese plum fruits. We evaluated the C and EC content in mesocarp and exocarp of samples from 79 and 64 seedlings of an F1 progeny (<‘98-99’ x ‘Angeleno’>) in the first and second season, respectively. We also constructed improved versions of linkage maps from ‘98-99’ and ‘Angeleno’, now calling SNPs after mapping already available GBS reads to Prunus salicina Lindl. cv. ‘Sanyueli’ v2.0 reference genome. These data allowed describing a cluster of QTLs in the cultivar ‘Angeleno’, associated with the flavan-3-ol composition of mesocarp and exocarp, which explain up to 100% of the C/EC ratio. Additionally, we developed a C/EC metabolic marker, which was mapped between the markers with the highest LOD scores detected by QTL analysis. The C/EC locus was located in the LG1, in an interval spanning 0.70 cM at 108.30 – 108.90 cM. Our results suggest the presence of a novel major gene controlling the preferential synthesis of C or EC in Japanese plum fruits. This work is a significant advance in understanding the regulation of synthesizing compounds associated with fruit quality, post-harvest, and human health promotion.